Vocational High School’s Students Motivation and Anxiety in Learning English at EFL Context - Alfila Maylani (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
English is difficult to study by foreign language students especially Vocational High School’s students because English has its own language structure which is different with Bahasa Indonesia’s language structure which is more complicated. As a result, students are not interested in learning English and they have anxieties in learning English. For example, feeling afraid of negative feedbacks of their participation in English class, feeling anxiety towards the, communication during English class, feeling terrified towards assessment in English class [1]. However, not at all students only have anxieties, some students also have motivation to learn English. There are two kinds of motivation, which are intrinsic and extrinsic. In this research, the writer uses descriptive qualitative method. The subject of this study was the first-grade students of SMK Negeri 4 Malang which consist of 35 students from X DG E class. The writer used two instruments which were questionnaire and interview for 4 selected students. The result of the questionnaire showed that the students intrinsic and extrinsic motivation was “high” with variable mean was 2.910. It was supported the result of interview; they intrinsically feel happy to learn English and they extrinsically learn English to pass the exam. Meanwhile, the finding of this research showed that the students’ anxiety was “low” with the variable mean was 2.427. It was supported the result of interview, that they do not feel anxious towards English class. Therefore, it suggests the students to maintain their motivation and eliminate anxiety in order to improve the students’ achievement in learning English.